Thin single crystal perovskite solar cells to harvest below-bandgap light absorption. Issue 1 (December 2017) - Chen, Zhaolai; Dong, Qingfeng; Liu, Ye; Bao, Chunxiong; Fang, Yanjun; Lin, Yun; Tang, Shi; Wang, Qi; Xiao, Xun; Bai, Yang; Deng, Yehao; Huang, Jinsong
Abstract The efficiency of perovskite solar cells has surged in the past few years, while the bandgaps of current perovskite materials for record efficiencies are much larger than the optimal value, which makes the efficiency far lower than the Shockley–Queisser efficiency limit. Here we show that utilizing the below-bandgap absorption of perovskite single crystals can narrow down their effective optical bandgap without changing the composition. Thin methylammonium lead triiodide single crystals with tuned thickness of tens of micrometers are directly grown on hole-transport-layer covered substrates by a hydrophobic interface confined lateral crystal growth method. The spectral response of the methylammonium lead triiodide single crystal solar cells is extended to 820 nm, 20 nm broader than the corresponding polycrystalline thin-film solar cells. The open-circuit voltage and fill factor are not sacrificed, resulting in an efficiency of 17.8% for single crystal perovskite solar cells. Thin films of halide perovskites are promising for solar cell technology but they do not perform well at the band edge due to the low optical absorption. Herein, Chen et al. fabricate a high efficiency single crystal perovskite solar cell with thicker single crystals to harvest the below-bandgap photons.